Pengaruh Faktor Lokasi dan Strategi Penetapan Harga Terhadap Pendapatan Outlet Juragan Es Teh (Studi Kasus di Kelurahan Gondangwetan) - Khasanh, Amaliya Nur; Pradikto, Sugeng (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2025)
This study aims to analyze the influence of price and location factors on business revenue at Juragan Esteh outlets in Gondangwetan Village. In the midst of increasingly tight business competition, business actors are required to be able to understand consumer behavior and factors that influence purchasing decisions. Price and location are two important aspects that can determine the success of a business in attracting and retaining customers. The research method used is observation and direct interviews with business owners to obtain information related to pricing strategies and business location selection. The results of the study show that affordable and varied prices can attract consumers from various circles, while strategic locations on the side of the highway facilitate access and increase business visibility. These two factors significantly contribute to increasing business revenue. Thus, a proper understanding of pricing strategies and location selection is very important in supporting the success and sustainability of small businesses in the beverage sector.